PYROGLUTAMATE FORMATION AT THE N-TERMINI OF ABRI MOLECULES IN FAMILIAL BRITISH DEMENTIA IS NOT RESTRICTED TO THE CENTRAL NERVOUS SYSTEM - Tomidokoro, Yasushi (2010)
Amyloid molecules harboring pyroglutamate (pGlu) residue at the N-termini are considered to be important for the development of cerebral amyloidosis such as Alzheimer’s disease and thought to be either spontaneously generated or being catalyzed by glutaminyl cyclase. Familial British dementia (FBD) is an autosomal dominant form of dementia neuropathologically characterized by parenchymal amyloid and preamyloid deposits, extensive cerebral amyloid angiopathy, and neurofibrillary tangles. FBD is caused by a stop to Arg mutation in the BRI2 gene, generating de novo created amyloid molecule ABri which accumulates in FBD brains but is not present in the normal population. Soluble ABri molecules present in the circulation of carriers of the BRI2 mutation are 34 amino acids long exclusively harboring Glu residue at the N-termini (ABri1-34E), whereas water- and formic acid-soluble ABri molecules extracted from FBD brains have abundant ABri species bearing pGlu residue (ABri1-34pE), suggesting that pyroglutamate formation occurs at the site of deposition. In order to further clarify the mechanism (s) of ABri deposition, we studied whether pyroglutamate formation indeed occurs outside the central nervous system taking advantage that FBD is also a systemic amyloidosis. Soluble and fibrillar ABri molecules extracted from systemic organs and analyzed biochemically using a combination of immunoprecipitation, mass spectrometry, and western blot analysis were oligomeric in size and contained a large proportion of ABri1-34pE. The data indicate that pyroglutamate formation at the N-termini of ABri molecules is an early step in the process of FBD amyloid deposition, and its formation is not restricted to the central nervous system.